The Influence Of Product Innovation And Price On Customer Satisfaction In Halodoc Health Application Services During COVID-19 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted to find out how much influence product innovation (X1) and Price (X2) on Customer Satisfaction (Y) on Halodoc application in Bandung. The method used in this study is a quantitative method with 100 respondents of Halodoc application users in Bandung with multiple regression analysis calculations processed in SPSS25 Windows software. The main data from the study used questionnaire surveys, and secondary data was obtained through journal publications, articles, and theory books. According to the results of this study shows that the variable Product Innovation (X1) and Price (X2) has a significant influence together on the variable Customer Satisfaction (Y). These results showed the researchers that halodoc application users in Bandung considered the perspective when assessing satisfaction in using a product such as Product Innovation and Price offered.